Th e global financal crisis: Learning from regulatory and governance studies: with the introduction of Bob Jessop - Arup, Christopher (Journal of Public Governance, 2018)
In his article, Christopher Arup analyses the impacts of different studies on the processes of shaping regulations, governance and responsibilities of corporations and their influence on the world’s economy prior to and during the recent global financial crisis. The author emphasizes the need for a greater democratic control of financial resources and, at the same time, calls for less dependence on finance capitalism in the fields of essential services, social security and environment protection.